Central bank digital currency and bank intermediation: Exploring different approaches for assessing the effects of a digital euro on euro area banks - Ramón Adalid; Álvaro Álvarez-Blázquez; Katrin Assenmacher-Wesche; Lorenzo Burlon; Maria Dimou; Carolina López-Quiles; Natalia Martín Fuentes; Barbara Meller; Manuel A. Mu\~noz; Petya Radulova; Costanza Rodriguez D'Acri; Tamarah Shakir; et al. (European Central Bank (ECB), 2022)
In July 2021 the Eurosystem decided to launch the investigation phase of the digital euro project, which aims to provide euro area citizens with access to central bank money in an increasingly digitalised world. While a digital euro could offer a wide range of benefits, it could prompt changes in the demand for bank deposits and services from private financial entities (ECB, 2020a), with knock-on consequences for bank lending and resilience. By inducing bank disintermediation, a central bank digital currency, or CBDC, could in principle alter the transmission of monetary policy and impact financial stability. To prevent this risk, options to moderate CBDC take-up are being discussed widely. In view of the significant degree of uncertainty surrounding the design of a potential digital euro, its demand and the prevailing environment in which it would be introduced, this paper explores a set of analytical exercises that can offer insights into the consequences it could have for bank intermediation in the euro area. Based on assumptions about the degree of substitution between different forms of money in normal times, several take-up scenarios are calculated to illustrate how the potential demand for a digital euro might shape up. The paper then analyses the mechanisms through which commercial banks and the central bank could react to the introduction of a digital euro. Overall, effects on bank intermediation are found to vary across credit institutions in normal times and to be potentially larger in stressed times. Further, a potential digital euro's capacity to alter system-wide bank run dynamics appears to depend on a few crucial factors, such as CBDC remuneration and usage limits.
Keywords: E42; E51; G21; 330; CBDC; digital euro; bank intermediation; bank runs